Chronology of the western world, 400-1000 A.D. - Erdoes, Richard (The Society [production company], 1984)
Examines the western Europe from the fall of Roman Empire through the great migrations throughout Europe. Looks at the influence of christianity and the church, and explores Byzantine art and architecture.